Students’ Reading Strategies During the Pandemic in Higher Education - Muhammad Hidayat; M Nurul Ikhsan Saleh (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
The purpose of this article is to analyze the perceptions and experiences of undergraduate students in using strategies for reading texts during the Covid-19 pandemic. Researchers chose to use qualitative research in this study with a case study approach. The participants involved were 14 undergraduate students at the State Islamic University of Sultan Maulana Hasanuddin, Banten, West Java, Indonesia where participants were selected using the snowball sampling method. Data was collected through in-depth interviews which were then transcribed in which the names of participants were written pseudonymously. The collected data is then analyzed by the thematic analysis method. This study found that reading activities during the pandemic have their challenges and advantages and students have started to tend to get used to reading texts on a screen rather than reading in printout form, although some of them still prefer to read in printout form. The five main strategies in reading texts that are commonly used by students during the Covid-19 pandemic are memory association, retelling, previewing, identifying the main idea, and habituation. Researchers conclude that the effects of the Covid-19 pandemic have forced undergraduate students to get used to reading texts in on-screen form and reading strategies are still varied. Therefore, this research implies that the teaching and learning process should accommodate many strategies in reading texts based on proficiency in English and not dominate just one strategy.